2011
DOI: 10.1016/j.jcf.2011.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Transient elastography and portal hypertension in pediatric patients with cystic fibrosis

Abstract: Elastography should be recommended for all cystic fibrosis patients with liver disease to follow its progression. A prospective study is needed to define an elastography threshold value that predicts the presence of EV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 21 publications
0
49
0
Order By: Relevance
“…However, the prognostic role of CFLD in adults is less certain, and disease progression after adolescence is rare [7], [26]. Previous studies consisted of mixed patient cohorts with a large proportion of pediatric patients [12], [13] or of CF children with portal hypertension [14]. Hence, the reported increase of liver stiffness in these CFLD patients may be related to the more severe course of pediatric CFLD while our results reflect a milder degree of liver damage in adult CFLD cases.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…However, the prognostic role of CFLD in adults is less certain, and disease progression after adolescence is rare [7], [26]. Previous studies consisted of mixed patient cohorts with a large proportion of pediatric patients [12], [13] or of CF children with portal hypertension [14]. Hence, the reported increase of liver stiffness in these CFLD patients may be related to the more severe course of pediatric CFLD while our results reflect a milder degree of liver damage in adult CFLD cases.…”
Section: Discussionmentioning
confidence: 53%
“…First results of transient elastography (Fibroscan®, TE) in cystic fibrosis revealed an elevated liver stiffness in patients with CFLD classified according to pathologic ultrasound criteria [12] and biochemical or clinical definitions [13]. In a case series, TE could reliably identify children with CFLD and portal hypertension [14]. First data with the recently developed acoustic radiation force impulse imaging (ARFI) technique revealed a high accuracy for the detection of liver cirrhosis in pediatric CF patients with portal hypertension [15].…”
Section: Introductionmentioning
confidence: 99%
“…Noninvasive methods such as transient elastography can also be used for the detection of fibrosis in patients with chronic liver disease [39,40] . Studies of pediatric patients have produced favorable evidence regarding the use of these techniques [40,[41][42][43] . A study evaluating the use of transient elastography in children with chronic liver disease found that this method had good capacity to discriminate between significant fibrosis, severe fibrosis and cirrhosis [40] .…”
Section: Investigationmentioning
confidence: 99%
“…However, detection of CF-associated liver disease (CFLD) is challenging. Many studies have been done in the recent years to assess the role of different non-invasive markers in assessing liver fibrosis and PHT in patients with CF [177][178][179][180][181][182] [181]. Furthermore, TIMP-1 had a high diagnostic accuracy for CFLD in adults.…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…Furthermore, TIMP-1 had a high diagnostic accuracy for CFLD in adults. The diagnostic sensitivities were increased when TE and the respective biomarkers were combined for the detection of CFLD and EV [182].…”
Section: Cystic Fibrosismentioning
confidence: 99%